1996
DOI: 10.1038/bjc.1996.605
|View full text |Cite
|
Sign up to set email alerts
|

Survival of patients with advanced urothelial cancer treated with cisplatin-based chemotherapy

Abstract: Summary The aim of the present retrospective study was to assess long-term survival after cisplatin-based chemotherapy in 398 patients with advanced urothelial transitional cell carcinoma (TCC) treated at seven international oncological units. Various combinations of cisplatin, methotrexate, vinblastine (or vincristine) and doxorubicin were used. The complete response rate according to the WHO criteria was 17%. Partial responses were obtained in 42% of the patients. The overall cancer-related 2 year and 5 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 19 publications
0
18
0
2
Order By: Relevance
“…A variety of chemotherapy regimens was administered to 59% of the patients. The present study established PS and AP as the major important prognostic factors, and confirmed that patients with liver metastases have a poor survival [4, 6, 8]. PS, AP, and presence of liver metastases were independent prognostic factors both in the group receiving chemotherapy and in patients receiving palliative radiotherapy or no treatment.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…A variety of chemotherapy regimens was administered to 59% of the patients. The present study established PS and AP as the major important prognostic factors, and confirmed that patients with liver metastases have a poor survival [4, 6, 8]. PS, AP, and presence of liver metastases were independent prognostic factors both in the group receiving chemotherapy and in patients receiving palliative radiotherapy or no treatment.…”
Section: Discussionmentioning
confidence: 68%
“…Age, sex, localization or histology of the primary tumor or primary treatment did not influence survival. Prior reports of the importance of age included patients receiving chemotherapy and have been contradictory [2, 4]. A significant impact of prior treatment and localization of the primary tumor on survival after recurrence has been demonstrated in two smaller studies [11, 28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, after a major response to chemotherapy, a small number of patients (4.3%) remained free of disease after long-term follow-up. This percentage of long-term survivors may be increased when postchemotherapy surgery or radiotherapy is performed in selected responding patients (Fossa et al, 1996;Dodd et al, 1999). The data showed that urothelial cancer is a disease sensitive to chemotherapy.…”
mentioning
confidence: 99%